Assessment of Noise Levels and Perceptions of Its Health Impact at Kejetia Market in Ghana - Lyndon N. A. Sackey; Lawrencia S. Y. Agyemang; Patrick E. Acheampong; Michael Afriyie Owusu; Jennifer Amoah (The Scientific World Journal)
Noise pollution in developing countries such as Nigeria and Ghana is causing adverse effects on citizens, including hearing impairment, sleep disturbances, adverse social behavior, and cardiovascular diseases. This study assessed noise levels at the Kejetia Market in Ghana and the perceptions of health impact. A sound level meter (JD-801A) was used to measure the noise levels at the various points in the market. Results showed that noise exposure levels were not within Ghana Environmental Protection Agency standards 2008, with sources including loud music, advertisements, human congestion, and vehicles. Respondents perceived noise pollution sources as annoyance, mental stress, sleep disturbances, lack of concentration, hearing, and cardiovascular effects. The study suggests that stakeholders and authorities should educate the public on the health effects of noise pollution.